Putusan Gugatan Class Action pada Kasus Gagal Ginjal pada Anak dalam Perspektif Keadilan dan Pertangungjawaban - Indri Marselina; Christin Septina Basani (Jurnal Hukum Lex Generalis, 2025)
Healthcare is a service industry that provides services to the public, including treatment, disease prevention, and health promotion. In 2022, a case of acute kidney failure in children caused by syrup contaminated with ethylene glycol (EG) and diethylene glycol (DEG) resulted in 326 victims, including 204 children who died. This incident prompted the victims' families to file a class action lawsuit against the drug manufacturer. This study uses a normative juridical method with a statutory, case-based, and conceptual approach to assess the effectiveness of class action lawsuits and the liability of business actors. Class action lawsuits are an effective legal instrument to provide access to justice for a large number of victims, achieving substantive justice. From a legal accountability perspective, business actors were proven negligent in fulfilling their obligations as stipulated in Law Number 8 of 1999 concerning Consumer Protection. In addition to compensation obligations, business actors can also be subject to administrative and criminal sanctions. This study emphasizes the importance of strengthening the drug monitoring system and implementing stricter legal accountability to ensure consumer safety and ensure justice for victims.